Phylogeny and Origin of Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency Mutations in Indonesia - Maria Omega; Ross T. Barnard (Indonesian Journal of Biotechnology, 2013)
The aim of this study is to analyze the relationship between the types of G6PD mutations found in Indonesia and the relationships of mutations found in Indonesia to those found in other countries. We summarize the distribution of G6PDs in West Indonesia and East Indonesia. Moreover, we use bioinformatics methods to construct phylogenetic trees and compare the sequences containing the regions amplifi ed by the commonly used PCR primer pairs. Previous work has shown that Mediterranean G6PD and Chinese CoimbraG6PDare distributed in West Indonesia, whilst G6PD mutations in East Indonesia are Jammu/ViangchanG6PD and Chinese Gaohe G6PD. G6PD Jammu/Viangchan was mostly distributed in Flores Island, East Indonesia along with G6PDGaohe. We constructed phylogenetic trees using the G6PD sequences from various regions in Indonesia and other countries. It appears from phylogenetic trees and percentages of identity that FloresIndonesian G6PD defi ciency (Jammu/Viangchan G6PD, originating in India) is 92.5% identical to the G6PD defi ciency of Chinese origin (GaoheG6PD). It was interesting to note that the genetic region containing the Javanese Indonesian G6PD defi ciency (MediterraneanG6PD, fi rst found in Italy) located in the western parts of Indonesia is closely related (99% identity) to the Chinese G6PD defi ciency(Coimbra G6PD). We concludethat G6PD mutations in West Indonesia are closely related to G6PD mutations from China. G6PD mutations in East Indonesia are also closely related to G6PD mutations from India and China, but more distantly, and to different types to those in West Indonesia. A prediction of protein structure was carried out which allowed visualization of the locations of mutation on the three dimensional structure of G6PD. Key words: G6PD, phylogeny, origin, genetic mutations